Analysis of Factors Influencing the Decision to Select Thai Nguyen University of Information Technology and Communication - Tuan, Bui Ngoc; Deswina, Melri; Darwin, Widya; Febrianti, Novi (Universitas Negeri Padang, 2025)
This article presents a study that aims to examine and analyze the factors that influence students' decisions in choosing the Thai Nguyen University of Information and Communication Technology. The research intends to assist universities in gaining a deeper understanding of the crucial factors that students consider when selecting a university. Consequently, this will lead to the development of more effective admission policies and strategies. The study involved collecting data from a random sample of first-year students at Thai Nguyen University of Information and Communication Technology during 2022. Data was gathered using questionnaires and both qualitative and quantitative research methods, utilizing SPSS 20 software. The findings from factor analysis indicated that a multiple regression model was suitable for assessing the factors that influence decisions to enroll in the Thai Nguyen University of Information and Communication Technology. Variables such as CSVC1 (Adequate classrooms meeting to learning needs), CSCV4 (Modern and well-equipped library with ample study materials), HP3 (Generous scholarships for various groups), VL3 (Supportive policies for employment during studies), DT2 (Curriculum aligned with social needs), DT4 (High-earning graduates), and DNGV1 (Highly qualified and standardized faculty) showed significant correlations with the dependent variable - students' career choices. The results demonstrated that the proposed model was well-fitted, with favorable levels of compatibility indices (CFI, TLI) and accuracy (GFI, RMSEA). Additionally, the outcomes of the Structural Equation Modeling (SEM) supported the appropriateness of the proposed model and its capability to explain the relationships between variables in the study. Based on these research findings, the article provides recommendations, including enhancing faculty quality, improving infrastructure and facilities, diversifying programs, and enhancing university information dissemination to elevate the quality and quantity of future admissions.